2014
DOI: 10.1177/0333102414550106
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and stroke: In search of shared mechanisms

Abstract: We discuss the possible practical implications of clinical and experimental data, such as aggressive risk factor screening and management, stroke prophylaxis and specific acute stroke management in migraineurs. However, evidence from prospective clinical trials is required before modifying the practice in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 180 publications
(219 reference statements)
1
66
0
7
Order By: Relevance
“…22 Cortical spreading depression, the physiologic correlate of migraine with aura, has also been suggested as an underlying link between migraine with aura and ischemic stroke. 23 Moreover, both animal models of familial hemiplegic migraine (FHM type 1 mutant mice), and inherited monogenic vasculopathies such as CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy), for which migraine with aura is a feature, support the hypothesis that transient hypoperfusion or ischemic depolarization is associated with increased stroke susceptibility and migraine. 24 Molecular genetics has revealed associations between migraine and genetic polymorphisms of angiotensin I-converting and enzyme, 5, 10 methylenetetrahydrofolate (MTHFR), suggesting the potential of shared genetic risks for stroke.…”
Section: Resultsmentioning
confidence: 93%
“…22 Cortical spreading depression, the physiologic correlate of migraine with aura, has also been suggested as an underlying link between migraine with aura and ischemic stroke. 23 Moreover, both animal models of familial hemiplegic migraine (FHM type 1 mutant mice), and inherited monogenic vasculopathies such as CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy), for which migraine with aura is a feature, support the hypothesis that transient hypoperfusion or ischemic depolarization is associated with increased stroke susceptibility and migraine. 24 Molecular genetics has revealed associations between migraine and genetic polymorphisms of angiotensin I-converting and enzyme, 5, 10 methylenetetrahydrofolate (MTHFR), suggesting the potential of shared genetic risks for stroke.…”
Section: Resultsmentioning
confidence: 93%
“…Speculated mechanisms consist mainly of vasospasm [19, 20], prolonged of cortical spreading depression [21], platelet hyperaggregability [22, 23], increased prothrombotic factors [24, 25], endothelial abnormalities [26, 27] and alteration of arterial function [28]. In addition, a recent systemic review and meta-analysis study [29] has reported an association between migraine with myocardial infarction, The study suggests that the association is more obvious and evident in women, which was in line with results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These 2 diseases, one seemingly benign and the second often severe and catastrophic, remain common neurologic disorders with a high socioeconomic burden [2•]. Stroke is the second most common cause of death worldwide and the third most common cause of disability [3, 4].…”
Section: Introductionmentioning
confidence: 99%